2018
DOI: 10.1172/jci.insight.98202
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous LRRK2G2019S induces parkinsonian-like pathology in a nonhuman primate

Abstract: Parkinson's disease (PD) is the second most prevalent neurodegenerative disease among the elderly. To understand its pathogenesis and to test therapies, animal models that faithfully reproduce key pathological PD hallmarks are needed. As a prelude to developing a model of PD, we tested the tropism, efficacy, biodistribution, and transcriptional effect of canine adenovirus type 2 (CAV-2) vectors in the brain of Microcebus murinus, a nonhuman primate that naturally develops neurodegenerative lesions. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 63 publications
0
33
0
Order By: Relevance
“…Furthermore, CAV has been successfully used in a broad diversity of cortical and subcortical projection pathways (Table 1). Even though rodents were used as the animal models in most of CAV applications in Table 1, recently, CAV was also successfully used in non-human primates ( Table 1; Mestre-Francés et al, 2018;Bohlen et al, 2019;Dopeso-Reyes et al, 2019). These studies validate the applicability of CAV as a gene delivery tool in nonhuman primates, facilitating the investigation of neural circuits in a more human-relevant model.…”
Section: Beneficial Properties Of Cav For Circuit Analysismentioning
confidence: 79%
“…Furthermore, CAV has been successfully used in a broad diversity of cortical and subcortical projection pathways (Table 1). Even though rodents were used as the animal models in most of CAV applications in Table 1, recently, CAV was also successfully used in non-human primates ( Table 1; Mestre-Francés et al, 2018;Bohlen et al, 2019;Dopeso-Reyes et al, 2019). These studies validate the applicability of CAV as a gene delivery tool in nonhuman primates, facilitating the investigation of neural circuits in a more human-relevant model.…”
Section: Beneficial Properties Of Cav For Circuit Analysismentioning
confidence: 79%
“…In the mouse lemur brain, we also found that it contained the most connected nodes. Given the importance of this network it was critical to characterize it in the mouse lemur, which is widely used as a model of neurodegenerative diseases (Kraska et al, 2011; Mestre-Frances et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This small animal (typical length 12cm, 60-120g weight) is arboreal and nocturnal. It has a decade-long lifespan and is a model for studying cerebral aging (Sawiak et al, 2014) and various diseases such as diabetes-related encephalopathy (Djelti et al, 2016), Parkinson’s disease (Mestre-Frances et al, 2018), or Alzheimer’s disease (Kraska et al, 2011). It has a key position on phylogenetic trees of primates and is used to investigate primate brain evolution (Montgomery et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A similar study using broadlyexpressing Ad5-LRRK2 vectors in mouse brain compared G2019S and another kinase-inactive mutation, D1994A LRRK2, revealing neuroinflammation and vacuolization in aged mice due to LRRK2 expression in glial cells (48). A recent study in the non-human primate, Microcebus murinus, using long-acting canine adenovirus type 2 vectors, revealed an equivalent level of neuronal loss induced by WT and G2019S LRRK2 but without evaluating kinase activity (49). Therefore, the contribution of kinase activity in these or any mutant LRRK2 animal model has not been clearly established.…”
Section: G2019s Mutation In Vivomentioning
confidence: 94%